PEMBERIAN EKSTRAK DAUN GANDARUSA (Justicia gendarussa Burm, F) MENINGKATKAN KUALITAS SPERMA MARMUT (Cavia cobaya) - Rusmiatik Rusmiatik (Fakultas Kedokteran Universitas Islam Al-Azhar, 2022)
Efforts to search for the ingredients or contraception and anti-fertility by using ingredients from plants, has many done by the experts. But not much done intensively so that the result is no satisfactory. One of the plant which is known and is often used as an anti-fertility is willow plants (Justicia gendarussa Burm.f.). This Research study with willow leaf extract treatment (Justicia gendarusa Burm.f.) on guinea-pigs (Cavia cobaya) in order to see its influence on the quality of the sperm. the results of the study showed that the administration of extracting the leaf willows (Justicia gendarussa Burm.f.) orally on guinea-pigs bull with the concentration of 10%, 20%, 30% during 35 day can affect the quality of the sperm on guinea-pigs. The larger the concentration of leaf extract willows (Justicia gendarussa Burm.f.) which led to a further decrease in the concentration of the sperm, sperm motility and sperm morphology guinea-pigs. The higher the concentration of the given cause more low pH sperm treatment groups when compared with the control group.